Plan estratégico para el mejoramiento del servicio del subcentro de salud pública código 12001 de Buena Fé periodo 2014-2017. - Tuárez Olivo, Maricela Viviana (2015)
This research was conducted at the Public Health Code Subcentro 12001 Buena Fe, which is located in Canton Buena Fe Province Rivers Region Costa del Ecuador in 2014. The development of the strategic plan for the improvement of service Subcentro Public Health Code 12001 Buena Fé, is the main objective and of great importance due to the ongoing need for continuous improvement of services provided to the community, this it becomes very important as it allows us to think and plan what we do during the year, evaluate and measure the changes that are being made and devise solutions to all the problems that arise. He was raised as General hypothesis: The existence of a strategic plan for improving the service will allow the user satisfaction in Subcentro Public Health Code 12001 in good faith, and as Specific hypotheses: Knowledge of strategic processes and analysis of the external and internal environment will help to make improvements in service quality and design strategies….